Synthesis, Spectroscopic and Biological Studies of a New Some Complexes with N-Pyridin-2-Ylmethyl-Benzene-1,2Diamine - Naji, Shaymaa H.; Abdul Karim, Lekaa K.; Mousa, Falih H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
N-Pyridin-2-ylmethyl-benzene-1,2-diamine (L) was prepared from the reaction of ortho amino phenyl thiol with 2 – amino methyl pyridine in mole ratio (1:1) . It was characterized by elemental analysis (C.H.N) , FT-IR , Uv – Vis , 1H , 13C-N.M.R . The complexes of the bivalent ions (Co , Ni , Cu ,Pd , Cd , Hg and Pb) and the trivalent (Cr) have been prepared and characterized too . The structural was established by elemental analysis (C.H.N) , FT-IR , Uv – Vis spectra , conductivity measurements , atomic absorption and magnetic susceptibility . The complexes showed characteristic behavior of octahedral geometry around the metal ions and the (N,N,N) ligand coordinated in tridentat mode except with Pd complexes showed sequare planer . α ,Kf,εmax for the complexes were estimated too. β for Co – complex was calculated . The study of biological activity of the ligand (L) and its complexes showed various activity toward staphylococcus aureus and E.coli.